REMOTELY PILOTED AIRCRAFT SYSTEMS OPERATIONS UNDER UNCERTAINTY CONDITIONS - Chynchenko, Yuriy; Shmelova, Tatyana; Chynchenko, Oksana (Proceedings of National Aviation University (archive), 2016)
The article deals with the analysis of the research conducted in the field of influence of uncertainty factorson remotely piloted aircraft systems operations. We reviewed the models suitable for estimation of uncertainty effecton remotely piloted aircraft systems operations. Principles of detailed assessment and further analysis of uncertaintyeffect on remotely piloted aircraft systems operations are proposed.